2009
DOI: 10.1097/pep.0b013e318196eb37
|View full text |Cite
|
Sign up to set email alerts
|

An Aquatic Physical Therapy Program at a Pediatric Rehabilitation Hospital: A Case Series

Abstract: Aquatic PT used as an adjunct to land-based PT interventions may be effective in improving outcomes in patients with physical disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 31 publications
2
52
0
9
Order By: Relevance
“…Yet, despite of the opportunities provided by the aquatic environment for improving physiological and motor performance, very limited research has been documented thus far measuring specific outcome effects with regard to walking. Recent aquatic training studies in small samples of children with CP reported some evidence with regard to improving walking endurance [24,25,28], functional mobility [24,28], and strength [24]. However, these studies used no comparative treatment conditions or metabolic measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, despite of the opportunities provided by the aquatic environment for improving physiological and motor performance, very limited research has been documented thus far measuring specific outcome effects with regard to walking. Recent aquatic training studies in small samples of children with CP reported some evidence with regard to improving walking endurance [24,25,28], functional mobility [24,28], and strength [24]. However, these studies used no comparative treatment conditions or metabolic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, strength training [18,20,21] is among the most often practiced approaches; however, in spite of gains sometimes observed in strength, the suitability of this training to promote walking in children with CP has only limited support [22,23]. Swimming and aquatic therapy have been suggested as beneficial activities for children with motor deficiencies, including those with CP, when applied at very early ages [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A recent case series discussed an aquatic therapy program and included a 2-year-old girl with oligoarticular JIA whose primary joint involvement was her left knee [42 ]. At baseline, the patient was on track with her motor milestones but had struggled to maintain skills due to pain.…”
Section: Exercise Capacity In Children With Juvenile Idiopathic Arthrmentioning
confidence: 97%
“…수중 치료는 부력, 정수압, 물의 점성, 와류 와 같은 수중 환경의 특성을 이용한 치료로 체중 부하를 최소화하여 관절에 부담을 주지 않고 근력, 지구력 등을 향상시킬 수 있으며 [7] 자세를 보조해 줄 수 있고 항 중력 움직임을 촉진시켜 지상에서 수행하기 어려운 움직임을 수행 할 수 있는 기회를 제공해 준다 [8]. 최근 수중 치료가 신체적으로 장애 를 가진 환자에게 사용되고 있으며 유연성, 관절가 동 범위 및 근력 증진 [9], 호흡 능력 [10], 보행 [11], 대단위 운동 기능 [12] …”
unclassified